Handling of impact forces in inverse dynamics in landing after a jump - Bisseling, R.; Hof, A. (ISB Congress, 2006)
The purpose of this study was to detect the real contribution of the ground reaction force (GRF) and segmental acceleration in the sagittal net knee moment during the first part of impact of a landing after a jump by comparing a standard inverse dynamic method (SM) with an accelerometer based inverse dynamic method (AM).